Istilah Kecantikan pada Kolom Komentar Akun @Tasyafarasya di Tiktok: Tinjauan Semantik - Eka Putri, Anisa; Usman, Fajri; Darmawan, Alex (Hasta Wiyata, 2026)
This study aims to describe beauty terms and their meanings in the comment section of the @Tasyafarasya TikTok account, categorized into the domains of cosmetics, skincare, and body care. The methods and techniques applied in this study follow Sudaryanto's three-stage research framework: (1) data collection, (2) data analysis, and (3) presentation of data analysis results. The data collection stage was carried out using the observation method (metode simak). This was followed by the basic tapping technique (teknik sadap) and advanced techniques consisting of the Non-Participatory Observation technique (teknik Simak Bebas Libat Cakap/SBLC) and the note-taking technique (teknik catat). Data were analyzed using two methods: the identity method (metode padan) and the distributional method (metode agih). The identity methods applied were referential and translational identity methods, using the basic technique of Determining Element Division (Pilah Unsur Penentu/PUP) and the advanced technique of Equalizing-Differentiating (Hubung Banding Membedakan/HBB). Meanwhile, the distributional method utilized the Immediate Constituent Analysis as the basic technique (Bagi Unsur Langsung/BUL) and the substitution technique (teknik ganti) as the advanced technique. Subsequently, the informal method was used to present the results of the data analysis. Based on the data analysis, the beauty terms found in the cosmetics (make-up) domain include foundation, lip liner, browcara, baking, cracky, cushion, and skin tint. In the skincare domain, the identified beauty terms are micellar water, acne prone, face wash, moist, sleeping mask, sunscreen, tone up, skin barrier, double cleansing, and sheet mask. Meanwhile, the beauty terms found in the body care domain consist of body lotion, sunblock, body scrub, lightening, whitening, brightening, and abu-abu (greyish).